PENGARUH VARIABEL KEUANGAN DAN NON KEUANGAN TERHADAP RETURN SAHAM SETELAH IPO DENGAN BESARAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Wibowo Wibowo; Stefano Rendy (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2006)
This Research target is to know factors of any kind of influencing income smoothing and its bearing to share performance (return and risk) public company in Indonesia. Data of this research are obtained from 30 company listed in Jakarta Stock Exchange which have been selected using (purposive) judment sampling method. Samples are classified to be smoother and non smoother using Eckel's model (1981). Eckel model classification in this research use three object of variable of income : operation income, income before tax, and income after tax. Test of one-sample kolmogrov smirnov, mann whitney, t-Test, and multivariate logistics are used for data analysing. The result of this research indicate that pursuant to coefficient variation of operating income and income before tax independent variable: company size, net profit margin (NPM), industrial sector, and winner/losser stocks not influenced income smoothing. Base on coefficient of variation of income after tax indicates that company size, net profit margin (NPM), and industrial sector not influenced income smoothing while winner/losser stocks influence income smoothing. And it also indicated no return diffferent between smoother and non smoother, than no risk different between them.